Epidemiologic and Genomic Analysis of the Severe Acute Respiratory Syndrome Coronavirus 2 Epidemic in the Nebraska Region of the United States, March 2020–2021 - Siedlik, Jacob A.; Watson, Cynthia J.; Raine, Morgan A.; Cheng, Anne V.; Goering, Richard V.; Stessman, Holly A. F.; Belshan, Michael (Frontiers in Microbiology, 2022)
COVID-19 emerged at varying intervals in different regions of the United States in 2020. This report details the epidemiologic and genetic evolution of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the first year of the epidemic in the state of Nebraska using data collected from the Creighton Catholic Health Initiatives (CHI) health system. Statistical modelling identified age, gender, and previous history of diabetes and/or stroke as significant risk factors associated with mortality in COVID-19 patients. In parallel, the viral genomes of over 1,000 samples were sequenced. The overall rate of viral variation in the population was 0.07 mutations/day. Genetically, the first 9 months of the outbreak, which include the initial outbreak, a small surge in August and a major outbreak in November 2020 were primarily characterized by B.1. lineage viruses. In early 2021, the United Kingdom variant (B.1.1.7 or alpha) quickly became the dominant variant. Notably, surveillance of non-consensus variants detected B.1.1.7 defining mutations months earlier in Fall 2020. This work provides insights into the regional variance and evolution of SARS-CoV-2 in the Nebraska region during the first year of the pandemic.